Random codekey selection using codebook without pre-shared keys for anti-jamming in WBAN. (April 2016) - Gopalakrishnan, Balamurugan; Bhagyaveni, Marcharla Anjaneyulu
Abstract: An implementation of Wireless Body Area Network (WBAN) plays an important role in the security of physiological data (e.g. ECG, EEG, etc.). On practical implementation, this WBAN faces physical layer attacks such as jamming and eavesdropping. These critical attacks cannot be defeated through conventional cryptographic methods. Thus, in order to counteract jamming and eavesdropping, spread spectrum techniques such as Direct Sequence Spread Spectrum (DSSS) and Frequency Hop Spread Spectrum (FHSS) have been adopted. The vulnerability in conventional spread spectrum is the requirement of pre-shared key between sender and receiver. But once the secret key is known to the jammer, then entire network is jammed. So to overcome the problem of pre-shared keys and to enhance the security of WBAN, the Random Codekey Selection using Codebook (RCSC) DSSS has been proposed in this work. The ratio of probability of breaking the code for 15 and 31 chip PN sequences of 100 trials is 56.86%. The RCSC DSSS can defeat the jamming attack with a high jamming probability of 0.18 for non-reactive jammers and 0.65 for reactive jammers with a codebook of size 500.